Complementary and Alternative Medicine Use in Children With Inflammatory Bowel Disease. Issue 2 (February 2019) - Phatak, Uma P.; Alper, Arik; Pashankar, Dinesh S.
Abstract : ABSTRACT: Complementary and alternative medicine (CAM) consists of products and practices that are not considered to be a part of conventional medicine. This article reviews pediatric studies on CAM in inflammatory bowel disease (IBD) along with relevant adult studies. Prevalence of CAM use ranges from 22% to 84% in children with IBD all over the world. CAM use in IBD includes diet changes, supplements, herbals, botanicals, and mind-body therapies. Common reasons for using CAM include severe disease and concern for adverse effects of conventional medicines. Despite widespread use, there are limited studies on efficacy and safety of CAM in children. Small studies suggest a favorable evidence for use of probiotics, fish oil, marijuana, and mind-body therapy in IBD. Adverse effects of CAM are reported but are rare. The article provides current state of knowledge on the topic and provides guidance to physicians to address CAM use in pediatric patients with IBD.